Dynamics of Foreign Direct Investment Manufacturing Sector in Indonesia - Saparuddin Mukhtar; Dicky Iranto; Riana Raudha Adni (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2019)
This research was conducted to determine the short-term and long-term effects between Gross Domestic Product, Interest Rates, and Inflation on Foreign Direct Investment in the manufacturing sector for the period 2004-2017. Study applied VECM (Vector Error Correction Model), secondary data obtained from Bank Indonesia, BPS, and Bappenas. Based on the statistical results it can be concluded that: first, GDP has a positive and not significant effect in the short term, then in the long run, it has a negative effect toward FDI. Second, in the short term interest rates have a negative and not significant while in the long term interest rates have a negative and significant effect on FDI in the manufacturing sector. Lastly, inflation has a negative and insignificant effect, while, in the long-run inflation has a positive and significant effect on FDI in the manufacturing sector.